Design and psychometrics of the family caregivers burnout inventory of older adults with chronic disease - Farokhmanesh, Kataneh; Shamsalinia, Abbas; Kordbageri, Mohammad Reza; Saadati, Kiyana; Ebrahimi Rad, Reza; Ghaffari, Fatemeh (Frontiers in Public Health, 2024)
Background Identifying the hidden and pervasive phenomenon of burnout among family caregivers of older adults with chronic disease requires the use of a valid and reliable tool tailored to the cultural structure of the target community. Therefore, the present study aimed to design and psychometrically evaluate the family caregivers burnout inventory (FCBI) of older adults with chronic disease. Methods This research is a sequential exploratory mixed-methods study focused on instrument design, conducted in Iran in 2024. The study employed classical theory, involving three stages to create a valid instrument: item design using inductive (semi-structured face-to-face interviews with 13 caregivers) and deductive (literature review) methods, tool design, and tool evaluation using face validity, content validity, construct validity [exploratory factor analysis (EFA) (N = 297) and confirmatory factor analysis (297 participants)], convergent validity, and reliability (internal consistency and stability). Data were analyzed using AMOS version 24 and SPSS version 26. Results Based on qualitative findings, participant quotes, and item adoption from other studies, a pool of 228 items was designed using a 5-point Likert scale (always to never). After several stages of review by the research team, 102 items remained. Following face validity (2 items), content validity (46 items), and construct validity (23 items due to factor loadings less than 0.4 and cross-loadings), 71 items were eliminated, leaving 31 items. EFA results indicated that the family caregiver’s burnout construct of older adults with chronic diseases comprises six factors include; “neurosis,” “feeling victimized,” “extreme fatigue and helplessness,” “neglect or abuse of self and others,” “adaptation deficiency” and “emotional separation” explaining 52.93% of the total variance. The fit indices showed acceptable model fit with the data. In this study, composite reliability and average variance extracted (AVE) for the six factors were greater than 0.7 and 0.5, respectively, and the (AVE) for each factor was higher than the composite reliability. Cronbach’s alpha coefficient for the entire scale was 0.975, and there was a significant correlation between test and retest scores (p < 0.001). Conclusion FCBI demonstrates suitable validity and reliability and can be used in various settings by health service providers to identify symptoms of burnout in family caregivers.